Effect of different forms of information produced for cancer patients on their use of the information, social support, and anxiety: randomised trial. Issue 7547 (5th April 2006) - Jones, R B; Pearson, J; Cawsey, A J; Bental, D; Barrett, A; White, J; White, C A; Gilmour, W H
Abstract: Objective To explore the hypothesis that different methods of selecting and printing information for cancer patients could improve emotional support by affecting interaction with others, and so lead to improved psychological wellbeing. Design Randomised trial with eight groups (three factors, 2′2′2). Data collected at recruitment and three month follow-up. Participants 400 patients starting radiotherapy, of whom 325 with breast or prostate cancer and complete anxiety and depression data were included in the analysis. Interventions Printed booklets: half had only general information from CancerBACUP about each patient's cancer and half had personalised information from the patient's medical record plus selected general information; half were composed of information chosen interactively by the patient and half were produced automatically with a larger volume of material; and half had additional advice on anxiety management and half did not. Main outcome measures Patients' views of the information, use of their booklets with others; change in reported social support; change in anxiety and depression. Results The larger booklets produced automatically were more likely to be found useful and to tell patients something new and less likely to be seen as too limited than the booklets produced interactively, but they were also more likely to overwhelm some patients. Personalised booklets were more likely than general booklets to tell patients something new. There was no difference in patients' perceived understanding of their cancer by any of the intervention factors. Patients with personalised information were more likely to show their booklets to others and to think it helped in discussing their cancer or its treatment. There were no major differences in social support, anxiety, or depression by any intervention factors. Conclusions Patients were more likely to show personalised information to their confidants than general information. Further research is needed into the effects of sharing information on patients' social support and anxiety. Trial registration US Government Clinical Trials Database NCT00127465